2019
DOI: 10.1002/advs.201901785
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Cocktail Induces Hematopoietic Reprogramming and Expands Hematopoietic Stem/Progenitor Cells

Abstract: Generation of hematopoietic stem/progenitor cells (HSPCs) via cell expansion or cell reprogramming has been widely achieved by overexpression of transcription factors. Herein, it is reported that without introducing exogenous genes, mouse fibroblasts can be reprogrammed into hemogenic cells based on lineage tracing analysis, which further develop into hematopoietic cells, by treatment of cocktails of chemical compounds. The chemical cocktails also reprogram differentiated hematopoietic cells back into HSPC‐lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…All of these findings suggest the possibility of reprogramming both cancer cells and neutrophils in the cancer microenvironment. Third, our experiments show that mature neutrophils are reprogrammed into multipotent progenitors in the presence of a chemical cocktail [ 185 ]. In other words, neutrophils have the potential to undergo cell reprogramming.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…All of these findings suggest the possibility of reprogramming both cancer cells and neutrophils in the cancer microenvironment. Third, our experiments show that mature neutrophils are reprogrammed into multipotent progenitors in the presence of a chemical cocktail [ 185 ]. In other words, neutrophils have the potential to undergo cell reprogramming.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Moreover, some chemical cocktail compounds can promote HSPC expansion. For example, valproic acid (VPA), a histone deacetylases inhibitor, has been reported to promote HSPC proliferation, and this effect is further enhanced by the addition of the GSK3β inhibitor [ 22 ]. HSCs are crucial in maintaining the repopulating potential in the fetal liver.…”
Section: In Vivo Expansion Of Hscs: the Disorders In The Hematopoieti...mentioning
confidence: 99%
“…In addition, Ye et al demonstrated that the strategy of chemically induced pluripotent stem cells was repeatable in different donor cell types ( Ye et al, 2016 ). Chemical reprogramming has unique advantages different from traditional reprogramming methods, and it also plays a great role in promoting the study of somatic reprogramming mechanisms ( Zhao et al, 2015 ; Zhao et al, 2018 ; Zhao, 2019 ; Zhou et al, 2020a ; Zhou et al, 2020b ; Ma et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%